Między utopią turyzmu a antyutopią nieautentyczności - trzy filmowe podróże po Islandii - Konefał, Sebastian Jakub (Wydawnictwa AGH, 2011)
The road movie is a genre associated with the American counterculture breakthrough of the late sixties, which both criticised the American way of life and in a sophisticated way also strengthened the capitalistic system. Icelandic road movie uses the semantics and syntactic known from the American productions by combining them with national and transnational components. Marked by irony, the postmodern perspective of such movies as Júlíus Kemp’s Blossi/810551, Fridrik Fridriksson’s Cold Fever and Sólveig Anspach’s Back Soon may be read as a visual invitation to get acquainted with the touristic utopian image of Iceland. However, the close reading of these productions can also indicate that they may be regarded as cultural texts that attempt to deconstruct the inauthentic images of the utopian island.

Kino drogi jest gatunkiem filmowym, związanym z amerykańskim przełomem kontrkulturowym końca lat 60. XX wieku, który balansował pomiędzy kontestowaniem American way of life a ukrytym umacnianiem systemu kapitalistycznego. Islandzkie kino drogi korzysta z elementów semantycznych i syntaktycznych, wykorzystywanych w produkcjach z USA, nasycając je cechami narodowymi i transnarodowymi. Dzięki nasyconej ironią postmodernistycznej perspektywie filmy, takie jak Blossi/810551 Júlíusa Kempa, Cold Fever Fridrika Fridrikssona i Back Soon Sólveig Anspach mogą być odczytywane jako audiowizualne zaproszenia do zapoznania się z wykreowanym dla potrzeb przemysłu turystycznego utopijnym obrazem Islandii. Jednak przy dokładniejszej lekturze produkcje te uznać można również za teksty kultury próbujące ów nieautentyczny obraz dekonstruować.
Between utopian tourism gaze and dystopian inauthenticity - three road movies about Iceland
Studia Humanistyczne AGH
Keywords: sociology of tourism; utopia; dystopia; socjologia turyzmu; utopia; Iceland; dystonia; Islandia; road movies; kino drogi